Comportamiento de la actividad agrícola y ganadera en la fragmentación de bosques del refugio de vida silvestre marino costera “Pacoche” - Poaquiza Alava, Diana Carolina (2023)
The Pacoche Coastal Marine Wildlife Refuge (RVSMC-Pacoche) located in Manabí province suffers strong anthropic pressures such as deforestation, therefore, the purpose of this research was to evaluate the agricultural and livestock activity in the fragmentation of the forest in the RVSMC-Pacoche. In order to study this relationship, the NDVI calculation analysis of satellite images were used for the years 2015, 2016, 2017, 2018, 2019 and 2021. For this, the global changes in vegetation were analyzed from the OLI and TIRS sensors, and the analysis of the cover layer and land use for the period 2000 - 2008 and 2008 - 2018 in order to determine the changes presented in the vegetation cover. The results determined that the soils linked to agricultural activities presented a slight decrease in their surface (229.91 ha between the years 2015 and 2021) and the deforestation of the forest cover for the periods under study was 205.97 ha of forests, from this total, 73% corresponds to transition from forests to agricultural lands, however, the latter presented a decrease in its surface of 363.65 ha, in agreement with the NDVI analysis. It is concluded that agricultural and livestock activity did not contribute to the fragmentation of the forest in the RVSMC-Pacoche.